2015
DOI: 10.1002/ejsp.2146
|View full text |Cite
|
Sign up to set email alerts
|

Emergent social identity and observing social support predict social support provided by survivors in a disaster: Solidarity in the 2010 Chile earthquake

Abstract: Survivors of disasters commonly provide each other with social support, but the social‐psychological processes behind such solidarity behaviours have not been fully explicated. We describe a survey of 1240 adults affected by the 2010 Chile earthquake to examine the importance of two factors: observing others providing social support and social identification with other survivors. As expected, emotional social support was associated with social identification, which in turn was predicted by disaster exposure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
203
2
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 196 publications
(244 citation statements)
references
References 66 publications
15
203
2
11
Order By: Relevance
“…Research shows that in emergency settings, those affected often consider themselves as members of the same group and start to draw on this membership to be active agents to face the common challenges and provide help to each other (Drury et al, ; Williams & Drury, ). SSI provides a basis for being motivated to give others (in the same group) support, for expecting support from them, and for being able to coordinate together to provide support for the whole group (Drury, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that in emergency settings, those affected often consider themselves as members of the same group and start to draw on this membership to be active agents to face the common challenges and provide help to each other (Drury et al, ; Williams & Drury, ). SSI provides a basis for being motivated to give others (in the same group) support, for expecting support from them, and for being able to coordinate together to provide support for the whole group (Drury, ).…”
Section: Discussionmentioning
confidence: 99%
“…A study of survivors of the 2005 London bombings suggested that SSI emerged among strangers through common fate; this emergent SSI was the basis of helping behaviour among these strangers (Drury, Cocking, & Reicher, ). SSI was found to be a predictor of both expected support and coordinated support among survivors of the Chile earthquake of 2010 (Drury, Brown, González, & Miranda, ). Also, Vezzali, Versari, Cadamuro, Trifiletti, and Di Bernardo () found that sharing distress increases identification, which suggests the relevance for refugees facing secondary stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus a study of the London bombings in 2005 found that shared social identity was the basis of support behavior among strangers (Drury, Cocking, & Reicher, 2009). In such studies, it appears that seeing oneself as a member of an affected community can create expectations of support which turn individuals into active agents capable of giving help and coordinating with others to achieve common goals (Drury, Brown, González, & Miranda, 2015;Williams & Drury, 2009). This analysis of the role of identities and groups in dealing with stress and creating wellbeing is part of the wider 'social cure' approach (Jetten, Haslam, & Haslam, 2012) of applied social psychology, some of which has been translated into field guides that takes this capacity for informal collective resilience into consideration in emergency humanitarian planning (North Atlantic Treaty Organization [NATO], 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Because all the items addressed the same issue of emotional and social support related to solidarity-based reactions towards Greeks (Drury et al, 2016) and loaded on a single factor, we calculated one solidarity index (a = .94). Participants were asked to indicate how they would react upon hearing a Greek person expressing anger related to the current economic situation.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, previous research showed that perceived common fate, such as in the face of a natural disaster, created a shared identity with outgroup members (Drury, Brown, Gonz alez, & Miranda, 2016). The common group categorization that would apply in this context could include countries that are heavily affected by the economic crisis in Europe (in this case, Greece and Spain).…”
Section: Studymentioning
confidence: 99%